Kontribusi Pemikiran Ibnu Sina terhadap Perkembangan Filsafat Barat dan Islam: Implikasinya dalam Pembentukan Kemampuan Berpikir Kritis Peserta Didik di Era Modern - Rosyida, Nur Ayisya; Rossidy, Imron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking skills are high-level abilities that are important for students in the modern era. However, these skills are still underdeveloped in the Indonesian education system, resulting in Indonesia ranking low in this area. Ibn Sina was a philosopher who made an important contribution to the development of critical thinking skills. This study aims to analyze the contribution of Ibn Sina's thoughts to the development of Western and Islamic philosophy and its implications for the formation of critical thinking skills in students. The method applied in this study is a qualitative method with a literature study. The data was analyzed using descriptive analysis of Ibn Sina's work, Kitab al-Syifa'. The results of the study show that Ibn Sina's thoughts, especially his concepts of the classification of science, metaphysics, and the theory of emanation, influenced Western philosophy and enriched the tradition of Islamic philosophy. The implication is that the division of theoretical and practical knowledge supports the development of students' critical thinking skills, enabling them to analyze, assess, and apply knowledge logically, creatively, and ethically.